(3QhVI GdWGdHjf hYeOI GdeJbjfs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdQGaYj , CHh GdbGSe YHO GdcQje Hf eMeO Hf YHO GdcQje GdQGaYj GdbRhjfj, GdQGaYj GdbRhjfj,J (B623 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdQLYg s
(3BNQgG (B:s
(3hEfg EPG EHJGY HgjeI HKef aj PeJg BNQ GdLRA GdNGeS s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs